Training for high level performance in women's collegiate volleyball: part I training requirements - Hedrick, A. (Strength and Conditioning Journal, 2007)
Volleyball played at a high level of competition is a physically demanding activity. To perform and compete at a high level requires that athletes be well prepared physically to meet the demands of the game. The purpose of this article is to discuss the physical requirements of collegiate women's volleyball and the need to emphasize specificity when designing a volleyball training program.